Works by Azerbaijani Composers for Young Pianists - Арзу Ісмайлова (Вісник КНУКіМ: Серія Мистецтвознавство, 2025)
The aim of the article is to study the methodological and artistic-aesthetic significance of piano works by Azerbaijani composers in the education of young pianists. Results. A crucial role in the establishment and development of the genre of children’s music was played by U. Hajibeyli and all subsequent generations of Azerbaijani composers: A. Zeynalli, G. Garayev, F. Amirov, A. Abbasov, J. Hajiyev, T. Quliev, A. Alizade, V. Adigozalov et al. These composers have skillfully synthesised national and European musical traditions, drawing upon global musical masterpieces created by R. Schumann, P. Tchaikovsky, C. Debussy, and other outstanding classics. The scientific novelty of the research grounds on the fact that for the first time, the author studies traditions and innovations in the creation of piano literature for children by Azerbaijani composers. Conclusions. The historical traditions laid down by U. Hajibeyli are currently actively developing and being creatively updated. In their concise piano miniatures, specifically composed for young pianists, the composers aim for a distinctly vivid and expressive imagery, providing ample room for the development of children’s imagination. The works created for children represent a methodically valuable and effective educational repertoire, as they take into account the specifics of national musical perception. The genre of music for children remains relevant in the creative output of Azerbaijani composers today.